SAT0384 Long-Term Safety of Anti-Tnf Agents in Patients with Spondyloarthritis and Potential Occult HBV: An Observational Multicenter Study on 131 Patients. (15th July 2016) - Giannitti, C.; Lopalco, G.; Vitale, A.; Anelli, M.G.; Fabbroni, M.; Manganelli, S.; Frediani, B.; Barone, M.; Galeazzi, M.; Lapadula, G.; Iannone, F.; Cantarini, L.
Abstract : Background: drugs targeting tumor necrosis factor-α (TNF) biological activity deal with an increased risk of infections. Few papers address whether TNF blockers in rheumatic patients with potential HBV occult infection are safe (1–9). Objectives: to evaluate the safety of anti-TNF agents in cases of spondyloarthritis with resolved hepatitis B (HBsAg negative, HBcAb±anti-HBs positive) through a close monitoring of a possible HBV reactivation and/or rise in the aminotransferase levels. Methods: the medical records for 992 outpatients with rheumatic inflammatory diseases attending two Italian Rheumatology Units between 2007–2015 were retrospectively reviewed for diagnosis of spondyloarthritis, current treatment with anti-TNF agents and seropositivity for past HBV infection. 131 patients (70 men, 61 women; mean age:60, 63±9, 59 years) were included in the study: 55 with ankylosing spondylitis, 65 psoriatic arthritis, 9 inflammatory bowel disease-associated arthritis, 2 non-radiographic axial spondyloarthritis. Mean disease duration was 98, 64±42, 60 months. 64 patients were currently in treatment with Etanercept (29 in monotherapy, 31 with MTX, 3 with SSZ, 1 with CsA); 32 with Infliximab (18 as monotherapy, 10 with MTX, 3 with SSZ, 1 with CsA); 31 with Adalimumab (16 in monotherapy, 12 with MTX, 2 with LEF, 1 with CsA); 4 with Golimumab (3 with MTX, 1 as monotherapy). 101 patients received only 1 TNF inhibitor (54 Etanercept, 27 Infliximab, 20 Adalimumab); 23 patients switched to a second and 7 patients switched to a third anti-TNF agent. 51 patients had concomitant prednisone <12, 5 mg/die. All 131 patients were anti-HBc+, of which 109 were anti-HBc and anti-HBs+. No patient was positive for HBV-DNA at baseline, none received antiviral therapy prior to or during anti-TNF treatment. Results: at the end of the follow-up (mean of 75, 50±33, 37 months of anti-TNF therapy), no case of viral reactivation was observed in anti-HBc+ patients, no matter anti-HBs positivity. HBV-DNA remained undetectable, HBsAg negative, aminotransferases normal, nor it was necessary to stop biologic therapy because of viral infection. Conclusions: our retrospective analysis supports the safety of TNF inhibitors for spondyloarthritis patients with a serological pattern of previous HBV infection during a follow-up >6 years. Pre-emptive antiviral prophylaxis is not necessary routinely, but strict monitoring for AST/ALT increase, as well as for changes in HBV serology and HBV-DNA, is necessary and seems a cost-effective approach to identify early viral reactivation, whose occurrence is low, but not negligible, and consequently start antiviral therapy. References: Kim et al. J Rheumatol 2010;2)Vassilopoulos et al. ARD 2010;3)Caporali et al. Arthritis Care Res 2010;4)Giannitti et al. J Rheumatol 2011;5)Lan et al. ARD 2011;6)Lee et al. Clin Exp Rheumatol 2013;7)Cantini et al. Int J Rheumatol 2014;8)Biondo et al. Eur J Intern Med 2014;9)Barone et al. Hepatology 2015 Disclosure of Interest: None declared